Theorizing lived religion: introduction - Knibbe, Kim Esther (Journal of contemporary religion, 2020)
The introduction to this special issue describes the emergence of the lived religion approach in relation to other approaches within the study of religion and sociology of religion as a way of going beyond the emphasis on texts and institutions, on the one hand, and the focus on the fate of religion in modern times, on the other hand. It also introduces the aim of this special issue, namely ‘theorizing’ lived religion. To do this, the authors summarize how the founders of this approach have conceptualized the topic of ‘lived religion’, adjacent approaches, and the theoretical underpinnings of their work. The authors propose three directions to develop the contribution a lived religion approach might make to theorizing: 1) explicating what is meant by ‘religion’ by drawing on work that studies religion as a category; 2) explicating how concepts and theories are developed based on lived religion research, with particular emphasis on the way tensions between modernist, disenchanting epistemologies and the enchanted, supernatural worlds of practitioners may inform theory and methodological reflection; 3) anchoring the doing of research, emphasizing the full research cycle in religious studies programs so that students have a solid basis for learning how to move back and forth between carrying out original research and conceptual/theoretical work.